Kecenderungan Depresi Ditinjau dari Kematangan Emosi dan Perasaan Putus Cinta Pada Mahasiswa - Krismiati, Firda Seftiana; Reza, Faisal Adnan; Tajuddin, Nilawati (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to determine the relationship between emotional maturity and feelings of breaking up with a tendency to depression in students of the 6th & 8th semester of geophysical engineering study program at the Sumatra Institute of Technology. The hypothesis proposed in this study is that there is a relationship between emotional maturity and feelings of breaking up with a tendency to depression. The measuring instruments used in this study include the Beck Depression Inventory (BDI), the Emotional Maturity Scale and the Breakup Feeling Scale. The results showed the correlation value (R = 0.851 and F = 88.238 with P = 0.000). These results indicate a relationship between emotional maturity and feelings of breaking up with a tendency to depression. Then, the results of the analysis were obtained with a value of rx1y = -0.766 and p = 0.000, which means that there is a significant negative relationship between emotional maturity and a tendency to depression. Also obtained the results of the analysis with a value of rx2y = 0.842 and p = 0.000 which means that there is a significant positive relationship between feelings of breaking up with depression tendencies. The effective contribution of emotional maturity and feelings of breaking up on depression tendencies is 72.5%, the remaining 27.5% is influenced by other factors outside this study.